THERMAL MANAGEMENT OF ELECTRIC VEHICLE BATTERY SYSTEMS - Dr. Praveen Kumar Yadaw,Ms. Soma Rajwade, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Electric Vehicles (EVs) have emerged as a pivotal technology for achievingsustainable transportation systems, yet the performance, safety, and lifecycle of EVs depends heavily on the thermal state of the battery system